Det kan vara farligt att ligga lågt - om stadsplanering inför stigande vattennivåer - Ebeling, Elisabet (2008)
In this study is being examined how cities can be planned in the face of rising water levels and extreme weather, due to the changing climate. The starting point has been to investigate how the problems can be tackled and how the positive sides of water in the city can be strengthened, and synergy effects and greater sustainability be achieved thereby. The method has been literature studies and case studies containing interviews and visits. Göteborg, Kristianstad and Arvika have been studied for discussions and ideas about adaptation. Today, building near water is very popular which brings both advantages and disadvantages. Attitudes towards water in the city have appeared, just as the managing of the situation, to be ambivalent. The cities show both similarities and differences in conditions and measures. The situation is handled differently because of natural prerequisites, experiences, organization, active individuals and political agenda, among other things. Spatial planning affects the city's vulnerability and robustness. The solutions available can be divided into planning for future settlements and measures concerning existing settlements. The two extremes are to either adapt the settlement to the water, or the water to the settlement. Synergy effects should be pursued for greater sustainability and robustness and can also be used as reinforcement of arguments for different measures. In the context of adapting cities to the future climate, the planner and/or landscape architect has an important function as a generalist and a creative force, in making change visible and participating in the public debate.